Association of photobiomodulation and topic hyaluronidase in paclitaxel extravasation: case study (Research, Society and Development, 2021)
Objective: To demonstrate the use of the association of photobiomodulation with topical hyaluronidase in paclitaxel extravasation. Method: Case study referring to the use of photobiomodulation and topical hyaluronidase in a paclitaxel extravasation that occurred in the oncology clinic of a university hospital. After 450 ml of paclitaxel infusion, the infusion pump stopped, edema on the site and displacement of part of the catheter from the puncture site was observed. Patient denied complaints of pain at the site and reported that he only observed the edema at the same time as the nursing team. The area was demarcated and presented an approximate measurement of 3.5 x 3.0 cm (height x width). Results: After verifying the extravasation, all necessary measures were taken, following the institutional protocol. Nine photobiomodulation points were performed using 1 joule/cm2 as energy density, then topical hyaluronidase 65 UTR/g was administered. The patient was instructed about home care. Conclusion: The association of FBM with topical hyaluronidase maintained the integrity of the patient's skin, not forming lesions resulting from extravasation.